A QUALITATIVE EXPLORATION OF INDIVIDUAL MOTIVATION FOR INTERMITTENT FASTING SUPPORTED BY EXERCISE USING SELF-DETERMINATION THEORY - Fadlilah, Ghaitsa Zahira Shofa; Ruhayati, Yati; Jajat, Jajat; Sultoni, Kuston; Suherman, Adang (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Obesity remains a global health issue with significant physical, social, and psychological impacts. One increasingly popular approach to managing obesity is the Intermittent Fasting (IF) diet. This study aims to examine the motivation and effectiveness of IF among fitness center members who also engage in regular exercise. Using the Self-Determination Theory (SDT) framework, this research explores internal and external factors influencing participants' commitment to IF.This qualitative descriptive study employed semi-structured interviews conducted at Idachi Fitness Metro Indah Mall. Thematic analysis following Braun and Clarke’s six-phase process was used to identify key themes. The findings revealed five categories of motivation: intrinsic regulation, identified regulation, introjected regulation, external regulation, and amotivation. Participants highlighted the benefits of IF, such as weight management, increased energy, and improved sleep quality. These findings underscore the importance of combining IF with exercise for achieving optimal health outcomes. Additionally, external motivations, such as social support and encouragement from trainers, often developed into intrinsic motivations as participants experienced health improvements. Further research is recommended to explore the long-term effects of combining IF and exercise on health and motivation.